Neuroscience nurses' comprehension of collaborating with and involvement of relatives: A qualitative interview study. (September 2022) - Guldager, Rikke; Loft, Mia Ingerslev; Poulsen, Ingrid
Within the field of neurological disease, it seems that involvement of relatives is of utmost importance since the patients often are affected in several areas (physical, cognitive, and emotional) which impair their ability to participate in decision-making about their treatment and care. This study aimed to illuminate neuroscience nurses' comprehension of collaborating with and involvement of relatives. Semi-structured interviews were conducted with 19 neuroscience registered nurses. The qualitative data were analyzed utilizing inductive thematic analysis. The COREQ checklist was applied. The analysis identified how collaboration with, and involvement of relatives are perceived as a focus for nursing care and a resource for both patients and registered nurses. Registered nurses having personal experience as a relative find it easier to establish a relationship with relatives. This study emphasizes the importance of the establishment of a trusting relationship between registered nurses and relatives for a positive collaboration and thus involvement of relatives.